Alignment with Indices of A Care Pathway Is Associated with Improved Survival: An Observational Population-based Study in Colon Cancer Patients. (October 2019) - te Marvelde, Luc; McNair, Peter; Whitfield, Kathryn; Autier, Philippe; Boyle, Peter; Sullivan, Richard; Thomas, Robert J.S.
Abstract: Background: Causes of variations in outcomes from cancer care in developed countries are often unclear. Australia has developed health system pathways describing consensus standards of optimal cancer care across the phases of prevention through to follow-up or end-of-life. These Optimal Care Pathways (OCP) were introduced from 2013 to 14. We investigated whether care consistent with the OCP improved outcomes for colon cancer patients. Methods: Colon patients diagnosed from 2008 to 2014 were identified from the Australian State of Victoria Cancer Registry (VCR) and cases linked with State and Federal health datasets. Surrogate variables describe OCP alignment in our cohort, across three phases of the pathway; prevention, diagnosis and initial treatment and end-of-life. We assessed the impact of alignment on (1) stage of disease at diagnosis and (2) overall survival. Findings: Alignment with the prevention phase of the OCP occurred for 88% of 13, 539 individuals and was associated with lower disease stage at diagnosis (OR = 0.33, 95% confidence interval 0.24 to 0.42), improved crude three-year survival (69.2% versus 62.2%; p < 0.001) and reduced likelihood of emergency surgery (17.7% versus 25.6%, p < 0.001). For patients treated first with surgery (n = 10, 807), care aligned with the diagnostic and treatment phase indicators (44% of patients) was associated with a survival benefit (risk-adjusted HRnon-aligned vs aligned  = 1.23, 95% confidence interval 1.13 to 1.35), better perioperative outcomes and higher alignment with follow-up and end-of-life care. The survival benefit persists adjusting for potential confounding factors, including age, sex, disease stage and comorbidity. Interpretation. This population-based study shows that care aligned to a pathway based on best principles of cancer care is associated with improved outcomes for patients with colon cancer. Funding: None. Putting research into context: Factors accounting for cancer outcome disparities both between within and between countries in well-resourced health systems remain elusive. In Australia, a nationally accepted evidenced based pathway of cancer care (the Optimal Care Pathway- OCP) has been developed through a multi-disciplinary clinician consensus based process, to establish the elements of quality care that should be offered to cancer patients. A project to assess the impact of the care that conforms with OCP standards on patient outcomes was undertaken. A robust survival improvement was seen in the group of patients whose care was aligned to the OCP. This improvement in outcome did not depend on new diagnostic tests or treatments. Alignment with pre-diagnosis pathway recommendations was associated with lower stage of disease at presentation, less emergency surgery and improved long term survival. These findings have policy implications as it is demonstrated that subtle system level variation of care could impact favourably on outcomes.